Fruit Growing - J.S. BAL; J.S. BAL (LUDHIANA KALYANI, 1994)
In this book on importance of fruits and scope of fruit growing ,selection of site and soil ,preparation of land,cultural practicesand flowering and fruiting are specially recent recommendation.
Fundamental Horticulture Tropical Fruits Sub-tropical Fruits Temperate Fruits
Keywords: Fundamental Horticulture, Tropical Fruits ,Sub-tropical Fruits